“Of Course, You Know Her!” (Pl. Phd. 60a). Xanthippe’s Presence by Socrates Deathbed - Guimarães, Leonardo (2024)
In Plato's Phaedo, when arriving to visit Socrates on his last day in prison, his friends and companions meet his wife, Xanthippe. This is the only time she is directly mentioned in the Platonic dialogues. The present paper aims to investigate the character of Xanthippe by going through the doxographic reception of the figure of Socrate's wife, a necessary path to reveal the social representation of the role of woman and wife entrenched in these views. Next, we will investigate the way the character Xanthippe is represented on the Platonic stage, in search of traces of a different representation of gender in the Platonic pages. One in which the figure of the woman, wife and mother Xanthippe is there to challenge Socrates and his philosophy.